Pre-existing and early cellular immune factors correlate with functionally complete protection against primary controlled human SARS-CoV-2 infection - Wagstaffe,HR; Thwaites,RS; Sidhu,JK; Lindeboom,RGH; Kretschmer,L; Worlock,KB; Dratva,LM; Huang,A; Ascough,S; Papargyris,L; McKendry,R; Collins,AM; et al. (Nature Communications, 2026)
Identifying host factors that mediate protection during first exposure to newly emergent viruses may assist in responding to future pandemics. Here, we report correlates of protection in a controlled human infection model of SARS-CoV-2 in serologically naïve individuals (n=34, aged 18-29 years) inoculated with 10 TCID50 of a D614G-containing pre-Alpha variant SARS-CoV-2. Eighteen developed “sustained infection” and seroconverted, while the remaining 16 did not. Pre-exposure and early immune factors associated with resisting infection were comprehensively analysed using multiplex protein, cytometric and RNA sequencing approaches in the upper respiratory mucosa and circulation. Associations between pre-existing antibody level and outcome suggested a modest role for cross-reactive antibodies in protection, with baseline nasal anti-SARS-CoV-2 Spike IgM levels correlating with delayed infection onset. Instead, resistance to infection was associated with heightened nasopharyngeal CCL13 levels produced locally by conventional dendritic cells and monocytes. Cross-reactive IL-2 producing T cells against SARS-CoV-2 non-structural proteins and less differentiated NK cells were also enriched at the time of inoculation in these individuals. This was followed by increased numbers of innate and adaptive cellsin the nasopharynx, including resident memory T cells, within 24 hours of virus exposure. Conditional independence network analysis revealed nasal CCL13 as the central node in a module associated with protection, connected to pre-existing RTC-specific T cells by CD1c+ DCs. In those who became infected, higher baseline cross-reactive T cell and less differentiated NK cell frequencies also correlated with shorter duration of infection. Thus, enhanced pre-existing mucosal chemokine levels may enable rapid immune cell recruitment and antigen-presentation to resident T cells in respiratory mucosa, effectively blocking infection. Where this local response fails to c